Effects of Fathers on Adolescent Daughters' Frequency of Substance Use and Risky Sexual Behavior. (22nd October 2020) - DelPriore, Danielle J.; Brener, Susan A.; Hill, Sarah E.; Ellis, Bruce J.
Abstract : This research: (1) implements a genetically informed design to examine the effects of fathers' presence–absence and quality of behavior during childhood/adolescence on daughters' frequency of substance use during adolescence; and (2) tests substance use frequency as mediating the relation between paternal behavior and daughters' sexual risk taking. Participants were 223 sister dyads from divorced/separated biological families. Sisters' developmental exposure to socially deviant paternal behavior predicted their frequency of tobacco, alcohol, and cannabis (TAC) use. Older sisters who co‐resided with fathers who were more (vs. less) socially deviant reported more frequent TAC use during adolescence. More frequent TAC use predicted more risky sexual behavior for these daughters. No effects were found for younger sisters, who spent less time living with their fathers.